Effect of Applying Potassumage and Banana Ash Combination as Bio-Fertilizers on Productivity of the Egyptian Wheat - Abou El Enin, MM - Abo-Remaila S.I - Maklad, K.M (Arab Journal for Sciences and Research Publishing, 2015)
Two pot experiments and field experiment were carried out at Agric. Res. Station, Fac. Agric., Al-Azhar Univ. Nasr City and El-Aleg region, Kaliobia governorate, Egypt, during 2011/2012, 2012/2013 and 2013/2014 to investigate the influence of K fertilizer packages as bio fertilizer on the productivity of wheat varieties. The three studied K fertilizer packages treatments were Potassiumag (bio fertilizer), Banana ash 4%, Potassumage +Banana ach 4% and control (without K fertilizer), as well as three wheat varieties (Sakha-93. Masry-1 and Banisweif). Complete randomized design was applied for the pot experiments, whereas, split plot design was conducted for the experimental field. Results showed significant differences between the three tested wheat varieties such as number of spikes/plant, number of grains/ spike, 1000 grains weight, yields of grains, straw and biological/yield per plant or per Fadden, as well as harvest index, Sakha 93 variety significantly surpassed Masr-1 and Baniswif-6 varieties in straw yield characters, while Masr-1 variety exceeded sakha-93 and Baniswif- 6 in grain yield characters. Moreover, Baniswif-6 gave grains quality characters higher than Sakha-93 and Masr-1 varieties in cache season under pot and field experiments. As for K fertilizer treatments, results showed that, significant differences were observed between the four studied potassium fertilizers packages for all studied characters under pot and field experiment in both seasons, whereas K4 treatments gave the highest values of growth, yield and yield components as well as technological characters. Also K3 treatment ranked the second and produced the highest values of the previous traits in both seasons. It worthy to mentioned that the differences between K3 and K4 treatments did not reach to the significant level. The interaction effect between the tested varieties and the studied K fertilizer packages was significant in most characters under study. Finally, applying 50% of recommended mineral K fertilizers with bio fertilizers (potassiumag + banana ash) are suitable fertilization treatment for maximizing the productivity of wheat varieties Sakha-93, Masr-1 and Baniswif-6 in pot or field experiments